Pengaruh Penggunaan Peralatan Kit Bahasa Inggris Dan Motivasi Belajar Bahasa Inggris Terhadap Prestasi Belajar Bahasa Inggris Siswa Kelas Iv Sd Negeri Impres Jalan Luku Tahun 2023 - Diana Viranty Surbakti (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Mastering a foreign language becomes a necessity in this globalization era. This is because language is a vital instrument to communicate with people thus in other words, it is called the tool to communicate. In the workplace, one of the requirements that someone must be able to fulfill is that they have to master a foreign language, or at least to understand the foreign language used in books as well as foreign products using foreign languages, especially since the global market has emerged. Therefore, , we are all indirectly required to be able to speak a foreign language in order to keep up with the development of the increasingly advanced era. The formulations of the problem in this research are: (1) How is the effect of the use of English Language KIT tools on the English learning achievement of fourth grade students at State Elementary Schools in Sumbergempol District?; (2) How is the effect of motivation of learning English on the academic achievement of fourth grade students at State Elementary Schools in Sumbergempol District?; and (3) How is the effect of utilizing the English Language KIT tools and the learning motivation as a whole on the learning achievement of English of fourth grade students at State Elementary Schools? This thesis is useful for the author to broaden the insight into the mindset, attitude, experience that is by understanding the nature of the effect of the use of English Language KIT tools and the learning motivation on the student achievement in the process of learning English, especially in elementary schools.